First chromosome characterization and repetitive DNA of Barred Gliding Lizard, Draco taeniopterus Günther, 1861 (Draconinae: Agamidae: Squamata) - Praween Supanuam; Sitthisak Jantarat; Warakarn Khawporntip; Thaintip Kraiprom; Somsak Bauthip; Sarun Jumrusthanasan; Sarawut Kaewsri; Nattasuda Donbundit; Sukhonthip Ditcharoen; Weera Thongnetr; Sumalee Phimphan; Alongklod Tanomtong (Caryologia)
This research was the first report on karyological analysis and distribution patterns of repetitive DNA using the fluorescence in situ hybridization (FISH) technique on the barred gliding lizard, Draco taeniopterus Günther, 1861. The 10 male and 10 female specimens were collected from Than To district, Yala province, Thailand. Chromosome preparation was performed by direct method using bone marrow and testis. The chromosomes were stained using conventional staining, NOR-banded, and FISH technique with d(GC)15, d(TA)15, d(CAG)10, and d(CAA)10 microsatellite probes. The karyotype of the barred gliding lizard reveals a diploid chromosome number of 34 and a fundamental chromosome number of 46, comprising of 8 pairs of large metacentric chromosomes, 2 pairs of small metacentric chromosomes, 2 pairs of large submetacentric chromosomes, and 22 pairs of microchromosomes, no sex chromosome detection between male and female karyotype. The metaphase I showed 17 bivalents and metaphase II showed haploid, n=17. The NOR is observed on the telomeric region of the last microchromosome pair 17th. Microsatellite repeat patterns indicate the presence of d(GC)15 and d(CAG)10 show specific regions, 2qter and 3qter respectively. While d(TA)15 and d(CAA)10, show cumulative signals dispersed throughout the chromosomes. This research can provide additional fundamental information for future genetic studies. The barred gliding lizard has the following karyotype formula: 2n=34=Lm8+Lsm2+Sm2+22mi.